Physical Properties Analysis and Quality Assessment of Gypsum-Kalsiboard Marketed in Ambon City - Rohny Setiawan Maail (Pattimura University Ambon Maluku Indonesia, 2021)
The objectives of this research were to analyse the physical properties and quality assessment of Gypsum Kalsiboard in the Ambon city market so that the physical properties of the boards and their quality are analysed and controlled. The material used was composite board in the form of gypsum-kalsiboard panels with length of 244.0 cm, width of 122.0 cm and thickness of 3.5 mm. This experimental model used Completely Randomized Design (CRD) and assessment the quality by control chart evaluated using 3-sigma control limits through the Upper Control Limit (UCL) and lower control limit (LCL). The result showed that the average of overall density was about of 1.41 g/cm3, moisture content of 9.12%, water absorption of 25.21% and thickness swelling about of 1.91% which meets the standard limits required by SNI No. 03-6434-2000. Although by quality assessment there were several points that are above the upper control limit (UCL) and below the lower control limit (LCL), the physical properties values of this board were still within the tolerance limits because the condition of the board does not show significant changes such as those related to water absorption and thickness swelling, indicating that the board was quite stable and high dimensional stability after 24 hours of immersion.